Reproductive Health of Rats with Benign Prostatic Hyperplasia Following Cosmos caudatus Ethanolic Extract Consumption - Dzulsuhaimi Daud, Nur Faza Mohd Fekery, Nooraain Hashim (Journal of Applied Pharmaceutical Science, 2017)
The purpose of this study was to determine the effect of Cosmos caudatus ethanolic extract on reproductive health of rats with testosterone-induced benign prostatic hyperplasia (BPH) by measuring daily urinary output, prostate volume, prostatic index and sperm parameters. BPH was induced by subcutaneous injection of testosterone undecanoate (3 mg/kg bwt), daily for 20 days. Then, 16 Sprague Dawley rats with BPH were divided into two experimental groups (n=8) and received 2 ml/kg bwt of distilled water (DW) and 250 mg/kg b.wt. of C. caudatus ethanolic extract (CCEE) daily for 20 days, respectively. Meanwhile, a group of healthy Sprague Dawley rats (n=8) served as a control and received 2 ml/kg bwt of DW daily for 20 days. At the end of the experimental period, urinary volume was recorded and all rats were euthanized by over-dose of diethyl ether. The prostate was quickly removed, cleaned and subjected to prostate volume and prostatic index determination. Epididymis also was collected for sperm parameters evaluation. The results showed that, CCEE increased the daily urinary output in rats with BPH. CCEE also reduced the prostate volume and prostatic index of rats with BPH. Meanwhile, sperm parameters were not affected by BPH and CCEE. These results suggest that CCEE demonstrated anti-BPH via anti-inflammatory without compromising sperm quality. Hence, C. caudatus represent a potential herb for the treatment of BPH.
Keywords: Cosmos caudatus, sperm parameters, benign prostatic hyperplasia (BPH), prostate volume, prostatic index.